The Semiotics of Furniture Form: The French Tradition, 1620-1840 - Fleming, John (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1999)
AbstractThis paper outlines and illustrates a few of the principles that might serve as a basis for a general semiotics of furniture form, meaning a description and analysis of domestic objects and utensils as a coherent system of signs related to human activity, to physical, social, and psychological needs, as well as to material context. The approach is both structural and inductive, anchored in specific examples drawn from French and English traditions between 1620 and 1840. The Louis styles are central to the argument, which proceeds from formal characteristics of shape, structure and immediate function to questions of aesthetic, psychological, and ideological intent.